Application Simplex Lattice Design on Optimizing Formula of Ketoprofen Matrix Patch Transdermal - Eka Indra Setyawan; Akhmad Kharis Nugroho; Achmad Fudholi (Journal of Food and Pharmaceutical Sciences, 2019)
Ketoprofen is a propionic acid derivative that has anti-inflammatory, analgesic, and antipyretic activity. Transdermal patch dosage form is the right choice for ketoprofen in an effort to minimize side effects, improving patient compliance and ensure the achievement of therapeutic targets. This study aimed to optimize the formulation of ketoprofen matrix patch transdermal. The optimizing process was analyzed by simplex lattice model. Determination of the level of ketoprofen released was carried out by spectrophotometer UV-Vis. Interpretation of the dissolution profile can be seen visually fit between the model constructed from the zero-order approximation, first-order, Higuchi, Korsmeyer-Peppas, Weibull, Hixson-Crowell and Baker-Lonsdale. The results provide information that a combination of MC and HPMC polymers have a significant influence on increasing the patch weight, patch thickness, loss on drying and dissolution efficiency and insignificant effect against folding endurance. The optimal formula is generated by a combination of HPMC:MC (0.1:0.9) and produces a patch matrix with weight, thickness, drying loss, and DE were 0.68 g, 0.36 mm, 12.42%, and 23.21%, respectively. The release kinetic of ketoprofen followed Korsmeyer-Peppas model through the mechanism of non-Fickian diffusion.